Patient Body Mass Index Does Not Predict Six-Month Clinical Outcome of Depression Managed Under Collaborative Care. (April 2013) - Angstman, Kurt B.; Wade, Todd W.; DeJesus, Ramona S.; Rundell, James R.; Altrichter, Paul M.
Obesity and depression are often comorbid conditions. There appears to be a bidirectional relationship between these. Obesity at baseline has been shown to increase the risk of onset of depression and depression at baseline increased the odds for developing obesity. Less is understood about the impact of obesity on depression treatment outcomes. The authors' hypothesis was that obesity (body mass index [BMI] ≥30 kg/m 2 ) and morbid obesity (BMI ≥ 40 kg/m 2 ) would each have negative effects on depression remission rates after 6 months of enrollment into collaborative care management for depression. In a retrospective analysis of 1111 depressed patients with a PHQ-9 (Patient Health Questionnaire) score of 10 or greater, multivariate analysis for the odds ratio of achieving remission at 6 months demonstrated that the patient's BMI at baseline was not an independent risk factor for depression outcome at 6 months. Collaborative care management for depression has been shown to be effective for improving depression outcomes, yet minimal prior research has focused on other clinical comorbidities that might affect outcomes. Although obesity was common in the study population, it was reassuring, based on this study that 6-month depression treatment outcomes do not appear to be significantly affected by the patient's baseline BMI.